2021
DOI: 10.24256/ideas.v9i2.2075
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers' Challenges in Classroom Management during Teaching Practice

Abstract: Classroom management is one of the most important aspects of teaching, in this case was English, to create an effective and enjoyable learning environment. However, this is one of the challenges faced by pre-service teachers who have no experience previously. This study was conducted to find out what challenges are faced by pre-service English teachers related to classroom management. This research was conducted on four English Education students who were selected based on several criteria. Qualitative researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, in facing these challenges, the ability of pre-service teachers in the aspects of self-control, self-management, and social skills is low such that they are less prominent in their attitude as leaders but prefer to be followers. Based on ( 9 ), there are three problems that are often faced by student-teachers related to students' bad attitudes and their learning motivation, including disrespecting the teacher, sleep during the class and lack of participation. The teachers' resilience level is also low, in addition to their lack of social skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in facing these challenges, the ability of pre-service teachers in the aspects of self-control, self-management, and social skills is low such that they are less prominent in their attitude as leaders but prefer to be followers. Based on ( 9 ), there are three problems that are often faced by student-teachers related to students' bad attitudes and their learning motivation, including disrespecting the teacher, sleep during the class and lack of participation. The teachers' resilience level is also low, in addition to their lack of social skills.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that the AQ levels of individuals tend to change over their lifetime ( 15 ). Besides, past research in the context of education has found that most teachers experience difficulties in changing their routines to adapt to changes ( 2 , 4 6 , 9 , 16 – 18 ). From pre-service teachers perspective, they are low-skilled in overcoming life's challenges because lack of vision, mission, and true meaning of life ( 19 ).…”
Section: Introductionmentioning
confidence: 99%